Effect of Structural Differences in Collagen Sponge Scaffolds on Tracheal Epithelium Regeneration. (February 2016) - Nakaegawa, Yuta; Nakamura, Ryosuke; Tada, Yasuhiro; Nomoto, Yukio; Imaizumi, Mitsuyoshi; Suzuki, Ryo; Nakamura, Tatsuo; Omori, Koichi
Objective: We developed an in situ regeneration-inducible artificial trachea composed of a porcine collagen sponge and polypropylene framework and used it for tracheal reconstruction. In the present study, collagen sponges with different structures were prepared from various concentrations of collagen solutions, and their effect on the regeneration of tracheal epithelium was examined. Methods: Collagen sponges were prepared from type I and III collagen solutions. The structures of the sponges were analyzed using scanning electron microscopy (SEM). Artificial tracheae, which were formed using the collagen sponges with different structures, were implanted into rabbits, and regeneration of the tracheal epithelium on the artificial tracheae was evaluated by SEM analysis and histological examination. Results: The SEM analysis showed that collagen sponges prepared from 0.5% and 1.0% collagen solutions had a porous structure. However, the sponges prepared from a 1.5% collagen solution had a nonporous structure. After implantation of artificial tracheae prepared from 0.5% and 1.0% collagen solutions, their luminal surfaces were mostly covered with epithelium within 14 days. However, epithelial reorganization occurred later on artificial tracheae prepared from the 1.5% collagen solution. Conclusion: Collagen sponges with a porous structure are suitable for regeneration of the tracheal epithelium in our artificial trachea.